2018
DOI: 10.22226/2410-3535-2018-2-169-173
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electronic properties of graphyne layers modeled on layers of graphene L3–12

Abstract: In the present paper, a theoretical study of the structure and electronic properties of new polymorphic conformations of graphyne layers modeled on layers of graphene L 3-12 was performed. Graphyne layers have been constructed by replacing carbon-carbon bonds between three-coordinated (sp 2-hybridized) atoms in the graphene layer of L 3-12 with diatomic carbyne chains. Geometric optimization and examination of electronic properties of novel graphyne architectures were performed within the framework of density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…% [10]. Therefore, many theoretical and experimental works have been carried out to find ways to increase the sorption capacity of carbon structures [11][12][13][14][15][16][17][18][19][20]. These works have demonstrated that reduction of the temperature and increasing of pressure have a very positive effect on the hydrogen storage by carbon structures.…”
Section: Introductionmentioning
confidence: 99%
“…% [10]. Therefore, many theoretical and experimental works have been carried out to find ways to increase the sorption capacity of carbon structures [11][12][13][14][15][16][17][18][19][20]. These works have demonstrated that reduction of the temperature and increasing of pressure have a very positive effect on the hydrogen storage by carbon structures.…”
Section: Introductionmentioning
confidence: 99%
“…The search of new carbon structures has not ceased over the past decades due to its unique properties found both in theoretical and experimental studies [1][2][3][4][5][6][7][8][9][10][11][12][13]. To date, carbon aerogels [1], crumpled graphene [2 -4], pillared graphene [5,6], moiré graphene bilayers [7], diamondlike carbon phases [9 -13] and many others have been experimentally synthesized or theoretically studied.…”
Section: Introductionmentioning
confidence: 99%